2016
DOI: 10.1177/1060028016683970
|View full text |Cite
|
Sign up to set email alerts
|

Increased Enoxaparin Dosing for Venous Thromboembolism Prophylaxis in General Trauma Patients

Abstract: Standard-dose enoxaparin prophylaxis may not be optimal for the general trauma patient population. Weight-based enoxaparin dosing (0.5 mg/kg/dose BID) is an option in trauma patients considered to be at a lower risk of bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 53 publications
5
62
0
1
Order By: Relevance
“…Finally, our data suggests most trauma patients will require enoxaparin doses higher than the current standard of 30 mg BID for VTE prophylaxis. This is consistent with recent literature and some have suggested increased empiric dosing or an initial weight-based enoxaparin dose 1,14. Unfortunately, this evidence base is still limited and there are no consensus recommendations concerning enoxaparin dosing for VTE prophylaxis in trauma patients.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, our data suggests most trauma patients will require enoxaparin doses higher than the current standard of 30 mg BID for VTE prophylaxis. This is consistent with recent literature and some have suggested increased empiric dosing or an initial weight-based enoxaparin dose 1,14. Unfortunately, this evidence base is still limited and there are no consensus recommendations concerning enoxaparin dosing for VTE prophylaxis in trauma patients.…”
Section: Discussionsupporting
confidence: 88%
“…The initial enoxaparin dose for trauma patients with a normal creatine clearance may also be based on weight. Options include 0.5 mg/kg twice daily, 51 , 52 0.6 mg/kg twice daily, 53 or 30 mg for 50 to 60 kg patients, 40 mg for 61 to 99 kg patients, and 50 mg for patients greater than 100 kg. 54 Patients who are initiated on higher doses of enoxaparin based upon weight should be monitored by anti-Xa levels because of the fluctuations in creatinine clearance after trauma that might lead to changes in the enoxaparin dose.…”
Section: Algorithmmentioning
confidence: 99%
“…This clinical pharmacist facilitated COVID-19 patients' ultrasound screening, diagnosis, and monitoring of prophylactic and full anticoagulation treatment. [18][19][20][21]47 This multidisciplinary team was adapted from previous programs that utilized a similar dynamic for management of trauma-related anticoagulation…”
Section: Discussionmentioning
confidence: 99%
“…In such models, the clinical pharmacist's duties include medication stewardship in addition to the screening, diagnosis, and monitoring of prophylactic and full anticoagulation treatment. [18][19][20][21] Since the start of the COVID-19 pandemic, experience from China, Europe and the United States has revealed that clinical pharmacists are essential for providing event-driven pharmaceutical care which goes beyond routine activities such as medication review, prescription support, and patient counselling. 13,14,[22][23][24][25] Here, the coordination of four-extremity screening ultrasound for all admitted COVID-19 patients was added to the workload of the clinical pharmacist.…”
Section: Introductionmentioning
confidence: 99%